2022
DOI: 10.3390/su14106335
|View full text |Cite
|
Sign up to set email alerts
|

Risk Network Evaluation of Prefabricated Building Projects in Underdeveloped Areas: A Case Study in Qinghai

Abstract: Prefabricated building projects (PBPs) face more risks than traditional construction projects, especially in underdeveloped areas. This study takes Qinghai Province as a study case. Social network analysis (SNA) is adopted to develop a risk network of PBPs, and nine core risk factors and five key risk relationships are identified. Risk effect detection reveals the effectiveness of risk response strategies. The research shows that PBPs in underdeveloped areas are still in the early stage of development, and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…While most of these studies assume a passive stance, by just documenting the evolution of networks [10,[15][16][17]36], some authors explore the dynamic potential of SNA by implementing changes to the network (structure, actors, ties) and documenting the impacts of those modifications in subsequent representations. The impact of these changes is measured in terms of resources, sustainability, governance [39], and risk performance [28,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While most of these studies assume a passive stance, by just documenting the evolution of networks [10,[15][16][17]36], some authors explore the dynamic potential of SNA by implementing changes to the network (structure, actors, ties) and documenting the impacts of those modifications in subsequent representations. The impact of these changes is measured in terms of resources, sustainability, governance [39], and risk performance [28,43].…”
Section: Discussionmentioning
confidence: 99%
“…The sources of data for the studies were also analyzed (Figure 4). Some articles refer to the use of mixed-methods approaches [19,[28][29][30][31][32][33], but the leading source was secondary data, with a 44% prevalence in the sample. Interviews (in-depth, semi-structured, and with experts) followed and were carried out in 31% of the studies.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gong et al also used social network analysis (SNA) to create a risk network but focused only on AC in less developed regions of China. the study found that AC in these regions is still in the early stages of development, and developers generally lack a dominant role [ 19 ]. Hsu et al developed risk models to capture changes in assembly site requirements for risk aversion but focussed on schedule risk.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The building life cycle theory [36] was proposed by Bekker in the 1980s, the essence of which was the material flow cycle in the construction process and all stages of construction activities. The construction project life cycle includes planning, design, construction, O&M, and demolition stages, which interact with each other [37]. Canto-Perello and Curiel-Esparza believed that O&M would become the key whole life cycle factor for UUT development [38].…”
Section: The Life Cycle Theorymentioning
confidence: 99%